E-Commerce Strategy for MSME Innovation Development in the New Normal Era - Novita Rifaul KIROM; Sudarmatin SUDARMIATIN; Agus HERMAWAN (Indonesia Strategic Sustainability, 2022)
The Covid-19 pandemic has had a significant impact on the growth and development of the world economy. Therefore, there needs to be changes or innovations that must make to improve economic conditions, one of which is through the development of online marketing (E-commerce), which has begun to be implemented by MSMEs in Indonesia. This study aims to determine the e-commerce strategy to increase the development of MSME innovation in the new normal era. This research shows that e-commerce readiness is very important in times of uncertainty, such as the COVID-19 pandemic. The level of readiness will determine the viability and sustainability of a company or business in a volatile business environment. E-commerce can evaluate readiness based on Technology Readiness, Organizational Readiness, and Environmental Readiness. However, not all perspectives are considered in making decisions about implementing or improving e-commerce during the pandemic.